Gonococcal arthritis: an unusual presentation as pseudothrombophlebitis. Issue 5 (May 1985) - Dawes, P T; Pattrick, M; Green, J
Abstract : A patient with a septic gonococcal arthritis of the knee presented as pseudothrombophlebitis.